Activin-A binding and biochemical effects in osteoblast-enriched cultures from fetal-rat parietal bone. - Centrella, M (1991)
Activin, a disulfide-linked polypeptide dimer first isolated from gonadal tissue extracts, has amino acid sequence and structural homology with transforming growth factor beta (TGF beta). Along with other activities, TGF beta regulates replication and differentiation and interacts with a defined set of binding sites on isolated bone cells. To determine if activin shares these properties, recombinant human activin-A (A-chain homodimer) was examined in osteoblast-enriched cultures obtained from fetal-rat parietal bone. After 23 h of treatment, 60 to 6,000 pM activin-A increased the rate of [3H]thymidine incorporation into DNA 1.5- to 4.0-fold, and at 600 to 6,000 pM, it enhanced the rate of [3H]proline incorporation into collagen and noncollagen protein by up to 1.7-fold. Like earlier studies with TGF beta in primary osteoblast-enriched cultures, the stimulatory effects of activin-A on DNA and protein synthesis were opposed by parathyroid hormone, and the influence of activin-A on collagen synthesis was independent of cell replication. Binding studies with 125I-activin-A indicated approximately 8,000 high-affinity (Kd = 0.4 nM) and 300,000 low-affinity (Kd = 40 to 50 nM) binding sites per cell. Polyacrylamide gel analysis revealed 125I-activin-A-binding complexes of Mr greater than 200,000 and 73,000 which did not appear to correspond to primary TGF beta-binding sites. These results indicate that activin-A produces TGF beta-like effects in bone and that some of these effects may be mediated, at least in part, by distinct activin receptors on bone cells.